Ibn Khaldun's Economic Thought; The Fair Tax And Its Relevance To The Modern Economy - Maulidizen, Ahmad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
This research is motivated by Ibn Khaldun's thoughts on taxes. According to Ibn Khaldun, if the tax is too low, the government cannot carry out its function, if the tax is too high, the fiscal pressure becomes too strong, so the profits of traders and producers decrease and their incentives to work are lost. The purpose of this study is to find out the concept of tax management that is fair to Ibn Khaldun's perspective to build a modern economy that is just and to know how the relevance of taxes according to Ibn Khaldun with today's modern economy. This research method uses library research methods with a type of descriptive qualitative research. The data source consists of the Muqaddimah as a primary source, work or theory that discusses primary material as a secondary and complementary material from primary and secondary materials as tertiary materials. The approach in this study is a historical and philosophical approach. The method of data collection uses existing literature and analysis of data used by analysis and hermeneutical content. This study concludes that the concept of a fair tax perspective Ibn Khaldun is a tax drawn from taxpayers in accordance with the ability of taxpayers to pay it and tax withdrawal money must be used properly and fairly, according to Ibnu Khaldun when the tax burden is light, people have incentives to try to be more active. Therefore, the business world is developing, which leads to greater satisfaction among the people because of the low tax burden, while tax revenues will also increase, judging from the overall source of tax land, Ibn Khaldun's thinking about taxes is very relevant when applied to modern economic conditions nowadays, where the economic conditions are less stable, the condition of society is increasingly difficult, the prices of expensive necessities of life add to the difficulties of people's lives.